Flexibility and robustness of a high-temperature air/ceramic thermocline heat storage pilot. (February 2019) - Nicolas, Lopez Ferber; Falcoz, Q.; Pham Minh, D.; Hoffmann, J.F.; Meffre, A.; Nzihou, A.; Goetz, V.
Abstract: A high-temperature air/ceramic thermocline packed-bed heat storage pilot was designed and built to measure the effects of operating parameters and quality of the heat resource on its performance, with a horizontal duct of square section. The influence of inlet air flow rate during the discharging phase and the impact of a degraded inlet heat resource during the charging phase were studied. The results revealed that the horizontal orientation of the bed didn't generate a thermal radial gradient. Results also show that the overall cycle efficiency is weakly affected by the changes in the operating conditions. Thermocline heat storage is surprisingly well-suited to managing resource instabilities. It forms a robust, flexible high temperature storage system applicable for industrial use to recover and deliver erratically produced waste heat.